2016
DOI: 10.1158/1078-0432.ccr-15-1250
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Prognostic Outlier Genes in High-Risk Prostate Cancer

Abstract: Purpose: There is a clear need to improve risk stratification and to identify novel therapeutic targets in aggressive prostate cancer. The goal of this study was to investigate genes with outlier expression with prognostic association in high-risk prostate cancer patients as potential biomarkers and drug targets.Experimental Design: We interrogated microarray gene expression data from prostatectomy samples from 545 high-risk prostate cancer patients with long-term follow-up (mean 13.4 years). Three independent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…Clinically, Decipher has undergone multiple validation studies with a total of > 2,000 patients and an AUC of 0.79. Patients who were deemed high risk with Decipher (GC ≥ 0.4) and received adjuvant therapy had improved survival 3, 36, 37, 38. Klein et al 36 evaluated the use of the Decipher GC with the National Comprehensive Cancer Network on 57 patients from a previous Decipher validation study from Cleveland Clinic.…”
Section: Prostatic Tissue Biomarkersmentioning
confidence: 99%
“…Clinically, Decipher has undergone multiple validation studies with a total of > 2,000 patients and an AUC of 0.79. Patients who were deemed high risk with Decipher (GC ≥ 0.4) and received adjuvant therapy had improved survival 3, 36, 37, 38. Klein et al 36 evaluated the use of the Decipher GC with the National Comprehensive Cancer Network on 57 patients from a previous Decipher validation study from Cleveland Clinic.…”
Section: Prostatic Tissue Biomarkersmentioning
confidence: 99%
“…Structural maintenance of chromosome 4 (SMC4) is a core subunit of condensin complexes, which chie y involved in chromosome condensation and segregation 49 . Overexpression of SMC4 is related to tumorigenesis and involved in tumor cell cycle, migration and invasion 50 .Previous studies have shown that SMC4 protein is highly increased in various tumors and correlated with poor prognosis of cancer patient [51][52][53][54][55] . However, its clinical signi cance and functional role in BC remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of FAM83D have been associated with poor outcome in several tumors and an increase in proliferation in vitro models [9, 10]. SMC4 belongs to a family of genes linked with poor outcome in prostate cancer [11], and finally, GTSE1 was described as associated with worse prognosis in uterine leimyosarcoma [12]. …”
Section: Discussionmentioning
confidence: 99%